2008
DOI: 10.1243/14644207jmda172
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene-carbon material for polymer electrolyte membrane fuel cell bipolar plates

Abstract: Bipolar plates are the interconnects between cells within a fuel cell stack. They must be highly electrically conductive in order to maximize the voltage across the stack and must be highly thermally conductive to aid cooling of the stack. Traditionally, bipolar plates are made from graphite or stainless steel; both have drawbacks such as low mechanical strength and corrosion problems, respectively. In order to overcome the problems associated with these common materials and to improve on the electrical and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…While the BPP must have high mechanical strength, low susceptibility to material dissolution, low susceptibility to the release of metal ions, and high corrosion resistance, the bulk electrical conductivity must be high and the interfacial contact resistance (ICR) must be kept low [120]. As an indication, targets set for mechanical strength and electrical conductivity are 44.26 MPa and 100 S/cm, respectively [121]. These attributes have to be achieved with materials and processes that are compatible with low cost and high volume manufacturability concepts.…”
Section: Resistance To Electron Transfer In the Bppmentioning
confidence: 99%
See 1 more Smart Citation
“…While the BPP must have high mechanical strength, low susceptibility to material dissolution, low susceptibility to the release of metal ions, and high corrosion resistance, the bulk electrical conductivity must be high and the interfacial contact resistance (ICR) must be kept low [120]. As an indication, targets set for mechanical strength and electrical conductivity are 44.26 MPa and 100 S/cm, respectively [121]. These attributes have to be achieved with materials and processes that are compatible with low cost and high volume manufacturability concepts.…”
Section: Resistance To Electron Transfer In the Bppmentioning
confidence: 99%
“…[125]. The conductivity of SS316 is, for example, ∼51 S/cm [121]. It has been shown that those grades of SS with a higher content of Cr and Ni, SS904L for example, result in the formation of thinner passive oxide films with low ICR.…”
Section: Stainless Steel Bppsmentioning
confidence: 99%
“…Several thermoplastic materials such as polypropylene (PP) , polyethylene , polycarbonate (PC) , and polyphenylene sulfide have been studied as the matrix for CPCs, including bipolar plate applications . Different carbon‐based fillers such as carbon fiber (CF) , graphite (G) , carbon nanotube (CNT) , and graphene (Gr) have been used as conductive fillers.…”
Section: Introductionmentioning
confidence: 99%
“…1 where the main aims were to decrease bipolar plate mass and cost and to increase mechanical strength whilst providing sufficient electrical and thermal conductivity. The study mixed high-density polyethylene (HDPE) with Monarch 800 carbon black 2 suitable for injection moulding and tested for the aforementioned properties.…”
Section: Introductionmentioning
confidence: 99%